Laporan Akhir Kerja Praktik (KP) Aplikasi Surat Perintah Perjalanan Dinas Di UPTD PPD Medan Utara Bapenda Provsu - Intan Nur Rafiqah; Fauzan Maulana Lubis; Muhammad Ikhsan (Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2023)
The Regional Revenue Agency (BAPEDA) is a government operational support component that carries out financial support tasks in the field of regional income. The author conducted a study of the official travel system while working practically, and at the UPTD PPD North Medan Bapenda PROVSU Medan produced an official travel order application. The author's aim in carrying out this practical work is to support the personnel department in the process of updating employee data including data entry and output. Assist in verifying car number plates and payment of vehicle tax that has just been registered on the e-Samsat application via the website with the branch office. Assist in preparing official travel orders and vehicle transfer reports. After a month of direct practice, the author found many incidents where after discussing with agency superiors, the author discussed the issue of Official Travel Orders (SPPD). The agency will use an inefficient and time-consuming system to handle future cases. because getting permission for official travel requires you to personally navigate a protracted bureaucracy. Therefore, the author used the skills he acquired in college to create an official travel booking system for an agency based on a website, making it easier for the department employees who handle it to obtain permits via the internet only. It can be concluded that students gain new information and experience through practical work that they would not get from face-to-face lectures. A clear picture of the overall scope of activities of an agency is provided through practical work. Additionally, practitioners receive training on how to perform their work with care, diligence, and analysis.